A study on students’ errors in using the English subjunctive mood. - Nguyen, Thi Hong Van (University of Languages and International Studies, 2017)
In order to advance subjunctive teaching and help students to grasp this grammar, a survey is conducted on English majors and non-English majors’ use of subjunctive. This paper is specificially aimed at figuring out the mistakes which first year students approach.